MIMIKRI DAN RESISTENSI PRIBUMI TERHADAP KOLONIALISME DALAM NOVEL JEJAK LANGKAH KARYA PRAMOEDYA ANANTA TOER: TINJAUAN POSKOLONIAL - Rusdian Noor Dermawan; Joko Santoso (Universitas Sarjanawiyata Tamansiswa, 2017)
This research aims to describe the process and form of resistance done by the natives to colonialism. This study belongs to qualitative descriptive research. The data are in the form of units of event containing the relations that include the process and form of resistance made by the natives to colonialism.Â The qualitative data used in this research are collected through observation, while the source of the data is a document in the form of novel Jejak Langkah published by Hasta Mitra Jakarta. The instrument used in this research is the researcher himself equipped with a set of postcolonial theory, particularly the concepts of mimicry and resistance. The technique used in collecting the data is observation, while the technique applied in analyzing the data is qualitative, descriptive, and interpretative one on the basis of postcolonial theories, mainly the theories of mimicry and resistance. In this novel, the resistance of the natives is done by the figure of resistance, that is Minke. The process of resistance begins with soft resistance called mimicry (language of technology and life devices,livelihood systems, arts, and systems of knowledge/ways of thinking). After reaching the power of quality to resist, the resistance is done radically, both through actual actions and textual productions.